PELAKSANAAN PEMBAGIAN KESELURUHAN HARTA KEPADA ANAK SEBELUM KEMATIAN PEWARIS DITINJAU DARI HUKUM ADAT DAN HUKUM ISLAM (Studi Penelitian Di Sei Bamban) - Hasibuan, Mhd Syahputra; Jamaluddin, Jamaluddin; Faisal, Faisal (Jurnal Ilmiah Mahasiswa Fakultas Hukum Universitas Malikussaleh, 2025)
Abstract This research examines the implementation of the distribution of all assets by the heir to their children before death, conducted by the Sei Bamban community, from the perspective of Islamic Law and Customary Law. This research aims to understand the traditional practices of inheritance distribution according to the customs of the Sei Bamban community and the legal consequences if the distribution is carried out before the heir's death. The method used is empirical legal research with a sociological and conceptual approach, descriptive in nature, with data collection techniques through field studies and literature studies, and analyzed qualitatively. The research results show that the practice of distributing assets during one's lifetime does indeed occur in Sei Bamban with the aim of avoiding family disputes after the heir's passing. In customary law, as long as it is carried out through deliberation and family consent, this division does not pose legal issues. Meanwhile, according to Islamic Law, the distribution of assets during one's lifetime is considered a valid gift if done voluntarily and with a complete transfer of ownership. However, if the gift is unfair or violates Sharia principles, it can be deemed invalid. In conclusion, the distribution of assets during one's lifetime should not diminish the rights of heirs according to applicable laws, and it should be supported by written guidelines from the government, customary leaders, and religious figures to provide legal certainty and prevent disputes in the future.